Increasing income-based inequality in suicide mortality among working-age women and men, Sweden, 1990–2007: is there a point of trend change?. Issue 11 (18th July 2018) - Hiyoshi, Ayako; Kondo, Naoki; Rostila, Mikael
Abstract : Background: Income inequalities have risen from the 1990s to 2000s, following the economic recession in 1994, but little research has investigated socioeconomic inequalities in suicide mortality for working-age men and women (aged between 30 and 64 years) over the time using longitudinal data in Sweden. Methods: Using Swedish national register data between 1990 and 2007 as a series of repeated cohort studies with a 3-year follow-up (sample sizes were approximately 3.7 to 4.0 million in each year), relative and slope indices of inequality (RII and SII respectively) based on quintiles of individual disposable income were calculated and tested for temporal trends. Results: SII for the risk of suicide mortality ranged from 27.6 (95% CI 19.5 to 35.8) to 44.5 (36.3 to 52.6) in men and 5.2 (0.2 to 10.4) to 16.6 (10.7 to 22.4) in women (per 100 000 population). In men, temporal trends in suicide inequalities were stable in SII but increasing in RII by 3% each year (p=0.002). In women, inequalities tended to increase in both RII and SII, especially after the late-1990s, with 10% increment in RII per year (p<0.001). Conclusions: Despite universal social security and generous welfare provision, income inequalities in suicide were considerable and have widened, especially in women. The steeper rise in women may be partially related to higher job insecurity and poorer working conditions in the female dominated public sector after the recession. To reduce health consequences following an economic crisis and widened income inequalities, additional measures may be necessary in proportion to the levels of financial vulnerability.